1、14+x=7 x+6=9 4+x=7+54+x-2=7 x-6=9 17-x=9x-6=9+3 9+3=17-x 16+2x =24+x4x=16 15=3x 4x+2=18 24-x =15+2x 2+5x=18+3x 6x-2=3x+103(x+6) =2+5x 2(2x-1)=3x+10 30-4(x-5)=2x-162(x+4) -3=2+5x 100-3(2x-1)=3-4x 30+4(x-5)=2x-2620x-50=50 28+6 x =88 32-22 x =10 224-3 x =3 10 x (5+1)=60 99 x =100- x 36 x=18 x6=12 56-2
2、x =20 36 x-2=16 x6+3=9 56-3x =20-x4y+2=6 x+32=76 3x+6=18 16+8x=40 2x-8=8 4x-39=29 8x-3x=105 x-65=42+2x 2x+5=7 32(x+3)+3=13 12x-9x=9 6x+18=48 56x-50x=30 5x=15(x-5) 78-5x=2832y-29y=3 5(x+5)=15 89 9x =80 3100-20x=20+30x 55x-25x=60 76y 76=1 23y 23=23 4x-20=0 80y+20=100-20y 53x-90=16 2x+9x=11 12(y-1)=24 80 5x=100 7x 8=14 65x+35=100 19y+y=40 25-5x=15 79y+y=80 42x+28x=140 3x-1=8-2x 90y-90=90-90y 80y-90=70 30 78y+2y=160 88-4x=80-2x 9 (4x)=1 20x=40 10x 65y-30=100 51y-y=100 85y+1=y+86 45x-50=40-45x 4